Applying the COM-B behaviour model and behaviour change wheel to develop an intervention to improve hearing-aid use in adult auditory rehabilitation - Barker, F; Atkins, L; De Lusignan, S (Taylor and Francis, 2016)
Objectives: To introduce a psychological model of behaviour; the COM-B model and describe how this has been used in combination with the behaviour change wheel (BCW) in developing an intervention which aims to promote regular, long-term use of hearing aids by adults with acquired hearing loss. Design: Qualitative structured interview study using the COM-B model to identify the determinants of behavioural planning on the part of audiologists; a potentially important factor in encouraging long-term hearing-aid use. Study sample: Ten audiologists drawn from a random sample of five English audiology departments. Results: The analysis suggests that behavioural planning might be more likely to occur if audiologists’ psychological capability, physical and social opportunity, and reflective and automatic motivation were addressed. This analysis forms the basis of an intervention design, using the BCW, to encourage behavioural planning by audiologists and subsequent hearing-aid use by people with hearing loss. Conclusions: The COM-B model and BCW can be applied successfully in the context of audiology to analyse the behaviour of both people with hearing loss and professionals working with them, supplying information that is being used in intervention design. The effectiveness of the intervention will be tested in a clinical trial.